Therapist–client relationships in a psychological therapy trial for psychosis and substance misuse. (1st July 2015) - Berry, Katherine; Gregg, Lynsey; Hartwell, Rosalyn; Haddock, Gillian; Fitzsimmons, Mike; Barrowclough, Christine
Highlights: Therapists' perceptions of improvement were associated substance use outcomes. Therapists' perceptions of improvements were not associated with symptom outcomes. Therapists' perceptions of improvement were related to alliance. Therapists' perceptions of alliance were unrelated to outcomes. Insecure attachment predicted outcomes for symptoms but not substance misuse. Abstract: Background: This study aimed to explore factors associated with outcomes in a randomised controlled trial of integrated motivational interviewing and cognitive behavioural therapy for psychosis and substance misuse. Method: Clients and therapists completed self-report measures of alliance and clients completed a self-report measure of adult attachment. Trial therapists were also asked to identify challenges in therapy, client strengths and reasons for client making and not making changes in relation to substance misuse. Results: Neither therapist-rated nor client-rated alliance was significantly related to objective outcomes. Client insecure attachment avoidance was associated with poorer symptoms and functioning at 12 and 24 months; although not changes in substance misuse. Therapists' perceptions of therapeutic processes (e.g., challenges to therapy, client strengths, client reasons for change and alliance) were consistent with previous literature. Therapists' perceptions of client improvement were associated with reductions in substance use at the end of treatment and their ratings of therapeutic alliance. Conclusion: Insecure adult attachment styles may be a potentially important predictor of symptom outcomes for people with psychosis and substance misuse. Trial therapists may also provide an important source of information about therapeutic processes and factors associated with outcome.